Fabrication and Measurement of a Circularly Polarized All-Metal Patch array and Single PRS Layer based Fabry-Perot Antenna for NASA Interplanetary CubeSat missions - Omari, Fouad; Benhmimou, Boutaina; Gupta, Nancy; El Khadiri, Khalid; Ahl Laamara, Rachid; El Bakkali, Mohamed (Journal of Applied Engineering and Technological Science (JAETS), 2025)
When it comes to pushing the limits of small-scale technologies for interplanetary space missions, NASA has demonstrated that the dream is achievable. NASA has launched a number of interplanetary CubeSat missions, including as MarCO A and B, INSPIRE, LOGIC, and LunaH-map CubeSats, successfully during the past 10 years. Since the antennas of these NASA-certified satellites are responsible for defining the range of communication with Earth, they are the main topic of this study. A high gain and circularly polarized all-metal patch array with PRS-based Fabry Perot antenna is proposed in this paper for NASA’s interplanetary CubeSat missions. The strength of this approach stems from its dependence on a wholly novel concept for developing a durable antenna that is harmoniously compatible with NASA's goals. The resulting all-metal patch array was well-fabricated and tested in an anechoic chamber and using a VNA, and showed measured realized gain of 35.84 dBi and AR of 1.629 dB at 11.5 GHz with 3dB-AR bandwidth higher than 3 GHz. Additionally, the Fabry-Perot design enhances the gains, achieves AR of 0.29 dB at 12.1 GHz, and exhibits RHCP and LHCP making this new technique as suitable candidates for NASA's interplanetary CubeSat missions.